2020
DOI: 10.1097/hjh.0000000000002279
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular, renal and liver protection with novel antidiabetic agents beyond blood glucose lowering in type 2 diabetes: consensus article from the European Society of Hypertension Working Group on Obesity, Diabetes and the High-risk Patient

Abstract: The prevalence of type 2 diabetes (T2D) has increased over the past few decades. T2D has a strong genetic propensity that becomes overt when a patient is exposed to a typical Western lifestyle, gain weight and becomes obese, whereas weight loss protects from the development of T2D. Except of lifestyle modifications, the choice of the appropriate treatment is essential in the management of patients with T2D and appears critical for the obese population with T2D. The new pharmacological approach for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 98 publications
1
34
0
2
Order By: Relevance
“…1 Obesity is associated with most cardiovascular risk factors, including metabolic syndrome (MetS), hypertension, type 2 diabetes, and dyslipidemia. 2 However, large interindividual heterogeneity in the development of obesity-related complications has been suggested. 3 Despite increased body fat, a subset of people with obesity do not have obesity-related cardiometabolic abnormalities; this is referred to as metabolically healthy obesity (MHO).…”
Section: Introductionmentioning
confidence: 99%
“…1 Obesity is associated with most cardiovascular risk factors, including metabolic syndrome (MetS), hypertension, type 2 diabetes, and dyslipidemia. 2 However, large interindividual heterogeneity in the development of obesity-related complications has been suggested. 3 Despite increased body fat, a subset of people with obesity do not have obesity-related cardiometabolic abnormalities; this is referred to as metabolically healthy obesity (MHO).…”
Section: Introductionmentioning
confidence: 99%
“…Second, SGLT2 inhibitors may contribute to better prognosis of HCC via improved liver function and preventing the development of hepatocarcinogenesis from NAFLD. SGLT2 inhibitors have been reported to ameliorate hepatic steatosis in patients with diabetes and non-alcohol fatty liver disease [19,42]. Recent studies have suggested that the stage of fibrosis is the most important predictor of liver outcomes, including HCC [43][44][45].…”
Section: Plos Onementioning
confidence: 99%
“…Besides their benefits in treatment of diabetes, SGLT2 inhibitors are considered to have additional renal and cardiovascular risk reduction benefits [16][17][18]. Because of these benefits, SGLT-2 inhibitors are recently being used one of the firstline drugs for glucose lowering, particularly in patients with type 2 diabetes at increased cardiovascular risk [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O DM2 tem uma forte propensão genética que se manifesta quando um paciente é exposto a um estilo de vida ocidental típico, ganha peso e se torna obeso (Kotsis et al, 2019).…”
Section: Introdução E Revisão Da Literaturaunclassified